O Processo de Aleitamento Materno em Bebês Prematuros e sua Relação com a Medicalização - Vieira, Tatiane da Silva (2018)
The public politics to maternal breastfeeding in Brazil, historically, brings as a goal the child mortality reduction. This public politics are based, mostly, in the organic and biological benefits that the maternal milk brings to baby's health. In several times, those studies and the public politics disregard historical, cultural and the experiences questions of this group of woman, those are dimensions just as responsible for the feed, and they justify this attitude for the baby’s health, quality and develop. In that meaning, the female body is understanding about the organically and reproductive point of view. The State, as it time, desire to control the society and the population develop by the body control, but they justify, implicitly, by their researches and scientifically innovations. This control gets into the maternal breastfeeding, emphasis that the woman should breastfeed. This way, actions are suggested to the maternal breastfeeding valorization, directed to the life quality, to the baby’s growing healthy and becomes a work force, serving the State, being productive. Foucault calls that as a biopolitical, an individual body who become social because is interesting to the economic and social development. The neonatal intensive care unit is the place where the premature new born receives necessarily cares to grew and develop, and through the NICU the premature and low weight baby’s life is ensure. In the context – baby plugged into equipment, necessity to use oxygen and specifically actions to guarantee the baby’s survive, the maternal breastfeed become one more attribution to the woman. The maternal breastfeed process become more delicate. Considering those questions, the principal objective was investigate the practical in maternal breastfeed and its relation with the medicalization in the dyad mother/baby internees in NICU. It is a descriptive research, qualitative design, approved by the ethical committee in searches. The triangulation method was apply by the combination between: the participant observation, the interview with the mothers and the interview with the health professional, employees in the NICU. The speeches were analyses together with the content analyses, thematic modality. The results revel the follow nucleus: “breastfeed and maternal insecurity: the professional hearing as a careful conduct”, maternal breastfeed and the NICU context: needs, demands and power relation” and “ the maternal breastfeed and the crossing medicalizations process: medicalizing or medicalized practices”? It was possible to note that the maternal breastfeed practical in NICU demand medicalizing and medicalized process, attached by the mother insecurity, her need to learn how to deal with the professional help in the first handling to took care in the basics needs and the maternal baby breastfeed. Although, it was question how much this medicalizing practical does not become excessive disciplinary, full of unnecessary rules, took off the freedom and the spontaneity of the act to breastfeed. The medicalization in maternal breastfeed is, definetelly a new subject and it should be considered in several contexts, no just into the NICU. The porpoise is make this subject identify, understand and with that, develop a new form to view about the help and care of the health professionals in the maternal breastfeed practical.